Determination of Rhizome Rate of Ramie [Boehmeria nivea (L) Gaud.] for Commercial Planting - SITANGSHU SARKAR; D.N. MAITRA (Seed Research, 2026)
A field experiment conducted during 1997 (pre-kharif)-2000 (rabi) with the aim to ascertain the exact requirement of ramie rhizome per ha revealed that 900 kg of rhizome (55,000 numbers, with mean weight, length and breadth of 14.823 g. 12.05 cm and 1.08 cm respectively) was needed for planting one hectare area.